Sistem Kamera Pengamatan Bawah Laut Berbasis Teknologi Cloud Computing - Pramana, Rozeff; Prayetno, Eko; Nugraha, Sapta (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
The camera is a popular device and easy to find in every human activities nowadays. The camera is not only known in the world of photography to capture images and video, but more than that. The camera has been used monitoring device that helps human works easier, more effective and more efficient. The camera has been used for security, to monitoring a place, traffic monitoring and other similar function in various sectors of human activity. Even now, the camera has been integrated with computer system and other systems to create a sophisticated automation control and monitoring technology. The purpose of this research is to design an underwater monitoring camera system that can display good quality video of underwater objek which can be displayed and accessed via internet using Youtube application. The main component of this design consists high resolution waterproof camera, microtic device, and computer. The communiction media used to access the internet network of this device uses 3G/LTE cellular signal. This devise produces good quality underwater video. The farther the camera is placed in the sea, the less the lighting and it results blurred image and limited range of vision.